Alternative Writing Worlds: The Possibilities of Personal Writing for Adolescent Writers - Johnson, Latrise P (Journal of adolescent & adult literacy, 2018)
Through the teaching of writing, classrooms are potential sites to address personal power, welcome student ideas, and cultivate a culture of writing for many purposes. Writing that is personal invites students to explore and compose what is possible and to make connections between a subject and the self. Such writing requires a reimagining of writing instruction that recognizes the personal nature of all writing and how writing might be used to connect the learner and learning. This article illustrates how inviting students to write their worlds provides many possibilities to not only center the lived experiences of students but also reshape their relationship to writing while writing about what matters to them in the here and now.